Inovasi Berbasis Lingkungan Melalui Pelatihan Pembuatan Hand Sanitizer Dengan Bahan Alami Di Desa Sumber Asri - Hervin Yoki Pradikta; Dian Resti Wulandari; Tiara Rica Dayani (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
During this Covid-19 pandemic, maintaining cleanliness is an obligation that must always be carried out by anyone at any time. Hand hygiene is an important thing that everyone must pay attention to, one of which is using a hand sanitizer. The community service activities regarding environmental-based innovation through training in making hand sanitizers with natural ingredients were carried out in Sumber Asri Village, East Buay Madang District, East OKU Regency. The purpose of this activity is to increase public knowledge about the benefits and advantages of using hand sanitizers with natural ingredients, empowering village potential, and so that people are able to make hand sanitizers independently. This activity begins with the stages of preparation, debriefing, and implementation. This activity is carried out face-to-face in stages from house to house, involving 10 heads of families. As a result, public knowledge about the benefits and advantages of using hand sanitizers with natural ingredients has increased. The community knows the potential of their village. People are also able to make hand sanitizers independently.